2014
DOI: 10.1007/s12522-014-0195-z
|View full text |Cite
|
Sign up to set email alerts
|

Clomiphene citrate affects the receptivity of the uterine endometrium

Abstract: A lower PR was shown by the patients who underwent thawed ET in the HRC within 90 days after their last CC treatment, which shows that CC affects the receptivity of the uterine endometrium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The negative impact of clomiphene citrate on endometrial receptivity was recently suggested by Nakagawa et al, 25 who reported lowered pregnancy rates in frozen-thawed IVF cycles up to 90 days after stimulation by clomiphene citrate.…”
Section: Discussionmentioning
confidence: 78%
“…The negative impact of clomiphene citrate on endometrial receptivity was recently suggested by Nakagawa et al, 25 who reported lowered pregnancy rates in frozen-thawed IVF cycles up to 90 days after stimulation by clomiphene citrate.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, clomiphene citrate is a highly potent prostaglandin synthesis inhibitor being comparable in this regard to indomethacin, thus raising concentrations of prostaglandin dehydrogenase in the endometrium [24] ; which negatively affects the implantation process. This was evident in the study of Nakagawa et al [25] who found that pregnancy rates following fresh embryo transfer for ovarian stimulation cycles using clomiphene citrate were poor (24.0%) even if hormonal treatment was given after clomiphene citrate treatment and endometrial thickness was recovered.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, no adverse effect of CC administration on pregnancy outcomes was observed after SVBT. A previous study reported that a cleaved ET, which included single and double embryo transfer, within 90 days after the last CC treatment resulted in a lower pregnancy rate compared with that for transfers at more than 90 days after CC treatment (Nakagawa et al , 2015). However, in their study, FSH and HCG were also used for ovarian stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Uncertainty remains regarding the duration of the effect of CC on uterine receptivity in the endometrium. Nakagawa et al (2015) previously demonstrated the long-term adverse effects of minimal ovarian stimulation with CC on pregnancy outcomes after either single or multiple ETs in a hormone replacement cycle; however, FSH and HCG were also used for ovarian stimulation, which may have affected their results. Moreover, their study included single and multiple ETs; thus, an evaluation of the actual effect of CC administration on uterine receptivity is challenging.…”
Section: Introductionmentioning
confidence: 99%